Peter Hocken: His Life and Work - Kay, William K. (Pneuma, 2015)
This article discusses the life and work of the Roman Catholic Charismatic Peter Hocken. It shows how, over many publications and in a series of writings directed both to Catholics and to the wider Christian world, he has constructed a theological understanding of the outpouring of the Spirit in the twentieth and twenty-first centuries. The purpose of the Spirit in denominational and nondenominational streams turns on the key role of Messianic Jews and is essentially eschatological and ecumenical as it prepares for the return of Christ. The article also includes a list of Hocken’s publications on Pentecostalism, charismatic renewal, and Israel.